2011
DOI: 10.3389/fncom.2011.00001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Gating the Flow of Information in the Cortex: What They Might Look Like and What Their Uses may be

Abstract: The notion of gating as a mechanism capable of controlling the flow of information from one set of neurons to another, has been studied in many regions of the central nervous system. In the nucleus accumbens, where evidence is especially clear, gating seems to rely on the action of bistable neurons, i.e., of neurons that oscillate between a quiescent “down” state and a firing “up” state, and that act as AND-gates relative to their entries. Independently from these observations, a growing body of evidence now i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 59 publications
(157 reference statements)
4
92
0
Order By: Relevance
“…A large number of studies in recent years has focused on subthreshold membrane resonance in neurons, its dependence on ionic currents and its influence on neuronal and network oscillations (Richardson et al 2003; Ledoux and N. 2011; Castro-Alamancos et al 2007; Tohidi and Nadim 2009; Izhikevich et al 2003; Engel et al 2008; Reinker et al 2004; Kispersky et al 2012; Moca et al 2012; Thevenin et al 2011). Subthreshold membrane resonance is primarily described on the basis of a linear RLC circuit where R is equated with the membrane resistance, C with the membrane capacitance and the inductance L , more abstractly, with voltage-gated ionic conductance properties (Erchova et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies in recent years has focused on subthreshold membrane resonance in neurons, its dependence on ionic currents and its influence on neuronal and network oscillations (Richardson et al 2003; Ledoux and N. 2011; Castro-Alamancos et al 2007; Tohidi and Nadim 2009; Izhikevich et al 2003; Engel et al 2008; Reinker et al 2004; Kispersky et al 2012; Moca et al 2012; Thevenin et al 2011). Subthreshold membrane resonance is primarily described on the basis of a linear RLC circuit where R is equated with the membrane resistance, C with the membrane capacitance and the inductance L , more abstractly, with voltage-gated ionic conductance properties (Erchova et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that the frequency of the network oscillations may crucially depend on the intrinsic preferred frequencies of the constituent neurons (Lau and Zochowski 2011; Wu et al 2001; Tohidi and Nadim 2009; Ledoux and N. 2011; Moca et al 2012; Sciamanna and Wilson 2011). These preferred frequencies arise in different contexts: the ability of a neuron to generate subthreshold oscillations at a particular frequency, often in response to a DC current input (Dickson and Alonso 1997; Lampl and Yarom 1997; Schmitz et al 1998; Reboreda et al 2003); the tendency of a neuron to produce subthreshold membrane potential resonance, a peak in the impedance amplitude in response to an oscillatory input current at a non-zero (resonant) frequency (Hutcheon and Yarom 2000); or membrane potential oscillations with zero phase lag in response to an oscillatory current input at a specific frequency (zero-phase-frequency).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, information-theoretic metrics such as Shannon mutual information have been used for channel ranking [13], [18], [19]. Methods for computing mutual information have been presented both for continuous-time neural signals [20] and for spike-trains using point process models [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…In one study a decreased BG-uptake of [ 18 F] fluoro-L-dopa was observed in patients with refractory TLE, and this could not be explained by structural changes alone (Bouilleret et al, 2008). Another study could show a projection of the BG onto the temporal lobe which was excitatory (Middleton and Strick, 1996; Gisiger and Boukadoum, 2011) and thought to have a substantial influence on motor areas (Mishkin et al, 1984; Petri and Mishkin, 1994, as cited in Middleton and Strick, 1996). Therefore, in our patient the disruption of this circuit may have led to a deficient excitatory input to the caudate nucleus.…”
Section: Case Studymentioning
confidence: 99%